Operative versus non-operative treatment of stable Weber type B ankle fractures with an intact syndesmosis - Omar Tareq Hussein Mahmoud Qashwa; Yasser Abdelfattah Radwan (2022)
(3JYJHQ cShQ CSad YXeI GdTXjI Ydi eSJhi GdoerQnJnHW yGdSfORehRiy ef CcKQ GdcShQ TjhYkG(B. (3h JhLO GdYOjO ef GdJUfjaGJ dgPG GdfhY ef GdcShQ(B, (3h WHbG dJUfja y OGfjS(B-(3hjHQy GdeSJNOe ai gPg GdOQGSI(B, (3jUfa gPG GdcSQ (B((3hjHQ ef GdfhY H(B). (3hdWGdeG cGf gfGc GdYOjO ef GdLOd Mhd eYGdLI gPG GdfhY ef GdcShQ LQGMjG Ce JMaXjG ddMUhd Ydi GdeQOhO GdhXjaj GdoeQVj ddeQjV(B. (3ai gPg GdOQGSI GdYThGFjIGdeVHhWI(B, (3JeJebGQfI GdYdGL GdLQGMj hZjQ GdLQGMj ddcShQ GdeSJbQI CSad YXeI GdTXjI Ydi eSJhi GdoerQnJnHW yGdSfORehRiy ai hLhO eQJHW Sdje(B, (3ef fGMjI GdeQOhOGdhXjai h GdLhOI GdUMjI ddeQjV HYO SJI CTgQ ef GdYdGL(B, (3h nNndUfG Edi Cfg dG jhLO aQb hGVM Hjf Cj ef GdYdGLjf HYO SJI CTgQ ef GdYdGL(B. (3h Ydjg jLH efGbTI GdMdhd GdYdGLjI h eejRGJgG h YjhHgG eY GdeQjV ddhUhd Edi GdYdGL GdefGSH GdCeKd(B.s
Thesis (M.Sc.)-Cairo University - Faculty of Medicine- Department of Orthopedic Surgery
Bibliography: p. 111-118.
Keywords: OrthopedicSurgery; Weber B